Occupational exposure to blood-borne or body fluid pathogens among medical interns at Addington Hospital, Durban - H. Karani; S. Rangiah; A.J. Ross (South African Family Practice)
Background: Healthcare workers are at risk of transmission of hepatitis B and C and human immunodeficiency viruses following accidental exposure to blood and body fluids. Interns are a vulnerable group of healthcare workers, cited as having the highest incidence of accidental needle-stick injuries and splashes with blood or body fluids. The main reason is thought to be a lack of experience and confidence, and underdeveloped dexterity skills, all of which increase risk of exposure. Since the introduction of the new two-year internship, to date no study has been carried out in South Africa comparing the incidence of occupational exposure between first- and second-year interns.